Antecedents and outcome of service recovery performance in service industry in Malaysia - Ng, Shu Ting; Tay, Yee Xin (2018)
Service recovery performance is efforts taken by organizations to bring back dissatisfied customers to a state of satisfaction. The purpose of this research is to study the antecedents and outcome of service recovery performance in service industry in Malaysia. The service industry in Malaysia is developing rapidly and it is seemed to be area of opportunity for additional research and new contributions. A total of 200 questionnaires have been distributed to the frontline employees who work in the service industry in Malaysia such as property, automotive, healthcare, insurance, banks and others. The sample is drawn by using convenience sampling where the respondents are most accessible. The data obtained are then analyzed by using SPSS version 23.0. The findings showed that customer service orientation, rewards, training, empowerment and teamwork are positively related to the service recovery performance; while effective service recovery is negatively related to frontline employees’ intentions to resign. This research implies that managers can better manage its frontline employees by focusing on the area of customer service orientation, rewards, training, empowerment and teamwork. However, the small sample size and location may limit the generalizability to the whole population of service industry in Malaysia. Hence, for future research, it is recommended to study the service recovery performance as moderator or mediator, taking into account of the potential antecedents and outcomes, in order to provide a comprehensive understanding of the whole service recovery process.